Relevansi Pembelajaran Berpusat pada Siswa dengan Pengembangan Kemampuan Berpikir Kritis dalam Pembelajaran Tematik Kurikulum Merdeka - Satria, Liza; Auji, Nurizam; Nainggolan, Guido (Journal of Practice Learning and Educational Development, 2026)
Primary education plays a crucial role in shaping critical thinking competencies as one of the key skills of the 21st century. However, the learning practices in elementary schools are still dominated by a teacher-centered approach, so the potential for students' critical thinking has not yet developed optimally. This article aims to critically examine the implementation of student-centered learning in the context of thematic learning within the Merdeka Curriculum. The method used is a critical literature review thru the Critical Book Review (CBR) and Critical Journal Review (CJR) approaches, by examining theoretical literature and recent empirical research. The study results show that student-centered learning aligns with the principles of constructivism, which positions students as active subjects in building knowledge thru experience, interaction, and reflection. The application in thematic learning, especially thru the problem-based learning model, discovery learning, and probing prompting, has proven effective in enhancing students' critical thinking skills, such as analysis, evaluation, problem-solving, and creativity. However, the effectiveness of the implementation highly depends on the readiness of the teachers, the quality of HOTS-based lesson planning, and the availability of media and supporting facilities. Some studies also show varying results, ranging from high to moderate categories, which emphasize the need to adapt strategies according to the school context. It is concluded that student-centered learning has both theoretical and practical relevance in enhancing critical thinking among elementary school students, provided it is supported by teacher competence and an adequate education system.